Women, land and power in Bangladesh : Jhagrapur revisited - Arens, Jenneke (Dhaka : University Press Limited, 2014)
On the women landownership issues in Jhagrapur, Bangladesh; a study.
Includes bibliographical references (pages 291-304) and index.
GenEd
Book Finder International
Keywords: Women in economic development -- Bangladesh -- Jhagrapur; Women landowners -- Bangladesh -- Jhagrapur -- Economic conditions; Economics; Bangladesh -- Economic conditions -- 20th century